Medicinal Earthworm: Speciation and Bioaccessibility of Arsenic and Its Potential Health Risks - Li, Yaolei; Li, Hailiang; Zan, Ke; Wang, Ying; Zuo, Tiantian; Jin, Hongyu; Zhang, Bing; Ma, Shuangcheng (Frontiers in Pharmacology, 2022)
Arsenic in environment and health has caused public concerns in the world. However, high levels of arsenic residues in medicinal animals have not received enough attention. Medicinal earthworms are consumed widely in China, but the arsenic's potential health risks to human are unknown. This work investigated the total concentration, bioaccessibility and speciation of arsenic in earthworm by ICP-MS and HPLC-ICP-MS to evaluate its potential health risks to human. Arsenic was found in all the earthworms at concentrations ranging from 0.4 to 53.6 mg kg-1. The bioaccessibility of arsenic varied significantly and was in the range of 12.1%-69.1%, with iAs (including AsIII and AsV) as the predominant species. And a small amount of AB was found. The estimated daily intake dose (EDI), hazard quotient (HQ) and carcinogenic risk (CR) of arsenic in most of samples were exceeded the safe threshold level. Results from this study indicated that the potential health risks by consumption of earthworm may not be negligible. Herein, recommendations for the use of earthworm and regulatory recommendations for arsenic limit standards were proposed. This study reminds us that more control and monitoring of arsenic in medicinal animals should be carried out.